Optimalisasi Literasi Numerisasi Siswa Sekolah Dasar Melalui Metode Multisensory - Muhammad Hasan Khoirudin; Deasy Andriani; Malya Safa Putriana; Muhammad Nofan Zulfahmi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This article reviews the importance of optimizing literacy and numeracy at elementary school level through the application of multisensory methods. Numeracy literacy is a very important aspect of basic skills for students, not only for academic success, but also for developing life skills in the digital and globalization era. This library research research method is often used in theoretical research, literature studies, or research that does not require collecting primary data through experiments or direct observation. Multisensory methods, which integrate various sensory channels such as visual, auditory and kinesthetic, have proven effective in supporting students to understand material more deeply and have fun. This approach can increase students' motivation and involvement in the learning process, as well as help them remember numeracy and literacy concepts better. This research shows that using a multisensory method approach, numeracy literacy learning in elementary schools can be more interesting and effective, providing a positive impact on students' cognitive development and problem solving abilities.